Development of an Android-Based E-Module for Basic Culinary Learning at SMK Istiqlal Delitua - Rendyka Eliadi; Waskito Waskito; Elida Elida; Riki Mukhaiyar (MASI Mandiri Edukasi, 2026)
The rapid advancement of digital technology has encouraged the integration of mobile-based learning media to enhance the quality of vocational education. However, previous studies have predominantly developed e-modules in PDF or web-based formats, which have not fully accommodated the practical learning needs of vocational education that require flexible access and integrated multimedia features. This study aimed to develop an Android Package (APK)-based e-module for the Basic Culinary course, focusing on Food Ingredients and Kitchen Equipment, for tenth-grade students in the Culinary Expertise Program at SMK Istiqlal Delitua. The study employed a Research and Development (R&D) approach using a modified Four-D (4-D) model comprising the define, design, and development stages, with the dissemination stage omitted. The product trial involved 34 tenth-grade culinary students. Data were collected through expert validation questionnaires, student response questionnaires, and learning achievement tests, and were analyzed using descriptive quantitative techniques. The results indicated that the developed e-module achieved media expert validation scores of 85.7% and material expert validation scores of 86.6%, both of which were categorized as very good. The practicality evaluation yielded an average score of 3.56, indicating a very good level of usability. Furthermore, students' mastery of learning improved from 64.7% in the first learning evaluation to 79.4% in the second learning evaluation after using the developed e-module. These findings suggest that the APK-based e-module demonstrates high validity and practicality and has the potential to support improved student learning outcomes within the context of this study. This research contributes to the development of digital learning media tailored to the characteristics of vocational education, particularly in Basic Culinary learning, and offers an alternative instructional resource to support smartphone-assisted independent learning.